Cross-Sectional Survey : The Influence of Various Teacher Backgrounds on West Kalimantan Chemistry TPACK Teachers - Permasari, Ninda; Nahadi, Nahadi; Hernani, Hernani (Universitas Tadulako, 2023)
This study aims to examine teachers' perceptions of their Technological Pedagogical and Content Knowledge (TPACK) about age, gender, length of teaching, work location, teacher status, teacher education, and certification programs. This study used a cross-sectional survey method used in non-experimental quantitative research. The population in this study were all chemistry teachers in West Kalimantan using a purposive sampling technique obtain 70 to respondents from 14 districts. The survey consisted of 28 statement items and distributed questionnaires via Google form to chemistry teachers. Chemistry teachers rated themselves on a 5-point scale. All domains of the TPACK framework demonstrated valid and reliable instruments on Pearson's correlation values and Cronbach's Alpha Kruskal Wallis non-parametric test, Pearson's correlation was performed to analyze the data. Significant differences can be seen in the CK domain when viewed from gender differences with a p for CK of 0.044, so there is a significant difference between the gender of women (Mean = 4.08 SD = 0.416) and men (Mean = 4.32 SD = 0.470). Location of work affects the teacher's TCK and TPACK because there is a significant difference when viewed from the p namely the TCK and TPACK of 0.036 and 0.025. Perceptions of teachers' TPACK abilities were greater for teachers in cities than in villages in both the TCK domain (Mean = 3.58; 3.82 SD = 0.430; 0.466) and TPACK (Mean = 3.63; 3.91 SD = 0.483; 0.554).